STRATEGIES FOR FORMING MEDIA COMPETENCE BASED ON BLENDED LEARNING - Tog’ayeva Muattar Bahodir qizi (TADQIQOTLAR, 2026)
Annotation: The rapid digitalization of education has significantly increased the importance of media competence as a key component of students’ professional and personal development. This article explores effective strategies for forming media competence through blended learning, which integrates traditional face-to-face instruction with digital and online learning environments. The study analyzes theoretical foundations, pedagogical approaches, and practical methods for developing media literacy, critical thinking, and digital communication skills. The research employs qualitative and mixed-method approaches, including observation, surveys, and experimental teaching. Results indicate that blended learning environments enhance students’ ability to critically evaluate media content, produce digital materials, and engage in interactive learning processes. The article concludes with recommendations for educators and institutions to optimize media competence development through blended learning models.